Bridging the gap between cytotoxic and biologic therapy with metronomic topotecan and pazopanib in ovarian cancer - Merritt, William M. (2010)
To investigate the anti-tumor and anti-angiogenic effects utilizing a novel therapy regimen of metronomic topotecan and pazopanib, a multi-receptor tyrosine kinase inhibitor. In vitro (Western blot) and in vivo dose-finding experiments were performed following pazopanib therapy in ovarian cancer models. Pazopanib and metronomic (daily) oral topotecan therapy was examined in an orthotopic model of ovarian cancer. Tumor weights, survival, and markers of tumor microenvironment (angiogenesis [CD31 and pericyte coverage]], proliferation [Ki-67], and apoptosis [TUNEL]) were analyzed by immunostaining following therapy. Pazopanib therapy reduced VEGFR-2 activity in vitro and vivo in a dose-dependent manner. Compared to control mice, pazopanib reduced tumor weight by 28-82% (p<0.01 in the SKOV3ip1 model) and metronomic topotecan reduced tumor weight by 40-59% in the HeyA8 (p=0.13) and SKOV3ip1 (p=0.07) models. Combination therapy had greatest effect with 79-84% reduction (p<0.01 for both models). In the SKOV3ip1 and A2780 models, mouse survival was significantly longer (p<0.001 vs. controls) with pazopanib and metronomic topotecan therapy. Pazopanib therapy reduced murine endothelial cell migration in vitro in a dose-dependent manner following VEGF stimulation and decreased tumor microvessel density and pericyte coverage when given in combination with metronomic topotecan. Tumor cell proliferation decreased in all treatment arms compared to controls (p<0.01 for combination groups) and increased tumor cell apoptosis by 4-fold with combination therapy. Pazopanib therapy in combination with metronomic topotecan therapy demonstrated significant anti-tumor and anti-angiogenic properties in preclinical ovarian cancer models and warrants further investigation as a novel therapeutic regimen in clinical trials.